The evaluation of activity of the Hospital Support Team in the Oncological Hospital - Jarosz, Jerzy; Wikłacz, Roman; Grzejszczak, Malgorzata; Czerwik-Kulpa, Marta; Smolik, Barbara; Opieka, Joanna; Markowska-Gąsiorowska, Anna; Majewska, Monika (Medycyna Paliatywna/Palliative Medicine, 2010)
There is a great need to integrate palliative medicine with oncology. It may secure possibility of ongoing care for each stage of treatment. The Hospital Support Team could be an integrative factor due to participation in hospital care, patient releasing procedures and assurance of proper home care procedures. The article describes the evaluation of the five-year activity of the first established Hospital Support Team in Maria Skłodowska-Curie Memorial Cancer Center – Warsaw Institute of Oncology in Poland. The scope of responsibility of palliative care specialists, especially educated nurses, psychologists and a social worker was evaluated. Based on the conducted consultations the qualitative and quantitative analysis was prepared by using our own Patients Expectation and Satisfaction Questionnaire – PESQ. The increasing demand for symptoms treatment and psychological care was well documented. In the symptoms treatment the main aim was to release pain. Nowadays, we additionally focus our attention on other symptoms such as: short breath, cancer cachexia, nausea and vomiting. Several times the team conducted palliative sedation. In reference to psychological involvement it was hard to evaluate particular effectiveness of interventions, nonetheless, their work got positive approval. Information concerning home care, medical equipment and social work consultations have emerged as especially important. The analysis of the five-year activities of the team indicates the significance of this kind of care and allows to recommend the Hospital Support Team as important and valuable structure of any Oncological Hospital.